Bandpass VHF range helical resonator filter - I. Yu. Malevich; D. A. Solonovich (Doklady Belorusskogo gosudarstvennogo universiteta informatiki i radioèlektroniki, 2019)
The results of the development and experimental verification of the bandpass helical resonator filter in the VHF range, made in the original design concept with improved manufacturability are presented.